2019
DOI: 10.1007/s11145-019-09978-z
|View full text |Cite
|
Sign up to set email alerts
|

Written verb use and diversity in children with Developmental Language Disorder: stepping stones to academic writing

Abstract: for their data collection efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 55 publications
4
15
0
Order By: Relevance
“…Our finding is also in line with the Connelly et al (2012) study, which revealed that the DLD group produced fewer words in their writing tasks compared to their TD peers. Furthermore, our results confirm the finding of Stuart et al (2020) in terms of the total number of words produced by the participants, while writing a text on a specific prompt and, also, are in line with Ralli et al (2021) who carried out their study in Greek. Ralli et al (2021) concluded that the DLD group performed worse than their TD peers of a corresponding chronological age in writing productivity measures as they wrote fewer words in their texts as compared to the TD group.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our finding is also in line with the Connelly et al (2012) study, which revealed that the DLD group produced fewer words in their writing tasks compared to their TD peers. Furthermore, our results confirm the finding of Stuart et al (2020) in terms of the total number of words produced by the participants, while writing a text on a specific prompt and, also, are in line with Ralli et al (2021) who carried out their study in Greek. Ralli et al (2021) concluded that the DLD group performed worse than their TD peers of a corresponding chronological age in writing productivity measures as they wrote fewer words in their texts as compared to the TD group.…”
Section: Discussionsupporting
confidence: 89%
“…Several researchers studied the total production of words of children with DLD while writing, using different control groups in order to identify if there was a significant difference among them or not. Mackie and Dockrell (2004) and Stuart et al (2020) agreed via their studies that DLD group produced fewer words in their written texts than TD children of a corresponding chronological age but not than those of a corresponding linguistic age. Dockrell et al (2007) concluded the same in their study in which only children with DLD participated and measurements were repeated twice within a gap of 2 years.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…This writing-by-language hypothesis would be supported if language proficiency largely determines writing quality and if there is a large gap in L1 and L2 language proficiency. Oral language skills are necessary for translating ideas and thoughts into language (Kim et al, 2011, 2014, 2015; Olinghouse, 2008; Olinghouse & Leaird, 2009; Silverman et al 2015; Stuart et al, 2020), and oral language skills are component skills that contribute to writing in DIEW (Kim, 2020; Kim & Graham, 2021; Kim & Park, 2019). Thus, lack of language proficiency will act as a bottle neck in the writing process and consequently in writing quality, and a large discrepancy in language proficiency between L1 and L2 will result in large differences in writing quality between L1 and L2.…”
Section: Writingmentioning
confidence: 99%